PHOTODEGRADATION OF Cr (VI) IN VARIOUS CONCENTRATION OF ZSM-5 IMPREGNATED TIO2 - Alfiani, Yulia; Mukaromah, Ana Hidayati; Sulistyaningtyas, Ayu Rahmawati (Universitas Muhammadiyah Semarang, 2018)
Nowadays,water could be contaminated by heavy metals such as chromium (Cr). Chromium toxicity depends on its state of valence. Cr (VI) as highly mobile is toxic, while Cr (III) as a less mobile is less toxic. Potentially, Cr (VI) content can be reduced by ZSM-5 impregnated TiO2. TiO2 as a catalyst can activated and modified zeolite with active metal materials. The impregnation between ZSM-5 and TiO2 should be reduce Cr (VI) content in water. The objective of this study was to assess concentration of ZSM-5 impregnated TiO2 which most effectively for decreasing Cr (VI) content. Decreasing Cr (VI) content in various concentration of ZSM-5/TiO2 was measured using UV-Vis spectrophotometer. The results showed that variation of zeolite concentration had an effect on decreasing Cr (VI) content in water. Photodegradation of Cr (VI) in various concentrations (0.25%;0.50%; 0.75%; 1.00%; 1.25% w/v) respectively are 16.99%; 18.84%; 24.83%; 30.82%; 36.14%. Concentration 1.25% w/v of ZSM-5 impregnated TiO2 as the highest to decrease Cr (IV) content. On the other hand, Using TiO2 or ZSM-5 only was showing lower percentage of Cr (VI) reduction which compared ZSM-5/TiO2. In conclusion, More higher concentration ZSM-5/TiO2 caused faster photodegradation and higher percentage decrease of Cr (VI) content in water. Keywords: Concentration, Cr (VI), Photodegradation, TiO2, ZSM-5